The anatomy of tweet overload: How number of tweets received, number of friends, and egocentric network density affect perceived information overload. Issue 4 (November 2015) - Sasaki, Yuichi; Kawai, Daisuke; Kitamura, Satoshi
Highlights We collected data through a web-based survey and through Twitter's open APIs. The number of friends had a significantly positive effect on tweet overload. The number of tweets received did not have a significant effect on tweet overload. A large number of friends strengthened network density's effect on tweet overload. A small number of friends strengthened network density but reduced tweet overload.